Surfaces and interfaces in natural fibre reinforced composites : fundamentals, modifications and characterization /: fundamentals, modifications and characterization. ([2018]) - Le Moigne, Nicolas; Otazaghine, Belkacem; Corn, Stéphane; Angellier-Coussy, Hélène; Bergeret, Anne
No abstract available